Prevalence of Pressure Injuries and Risk Factors in Long-Term Surgical Procedures - SAYIN, YAZİLE; Akan, Cemile; SAYIN, Yazile (My University, 2021)
Objective: To determine the risk factors and prevalence associated with intraoperative pressure injury (IPI) in surgical procedures lasting more than two hours, and to draw attention of surgical nurses to the prevention of IPI. Methods: This cross-descriptive study included 170 patients in whom major surgical procedures were planned in a private foundation university hospital's orthopedics and general surgery departments between February 2017 and May 2018. The study was approved by the ethics committee and informed written permission was obtained from the institutions and volunteers. Data were collected by using Braden Risk Assessment Tool (BRAT) and literature based patient diagnosis form. Results: The mean age of the participants was 47.72 +/- 22.20 years, 55.9% were female and 44.1% were male. Of the participants, 81.8% underwent surgery in the supine position, with a mean surgery duration of 246.707 +/- 145.3 minutes. Of the patients 24.1% developed stage 1 IPI. Forty-one (24.2%) patients with pressure injury had a lower BRAT score (18.434 +/- 6.621) than 129 (75.8%) patients without pressure injury (20.243 +/- 3.954), (p=0.035). According to multivariate analysis, both preoperative additional nutritional requirement and low albumin level increased the risk of IPI by 2.4 fold (p=0.038; 0.043, respectively). Each one hour of prolongation in duration of surgery increased the risk of IPI by 1.007 times (p=0.002). Conclusion: The risk of development of IPI is high in major surgical procedures. In determining the risk of IPI, the patient's nutritional deficiency, low albumin level, length of duration of surgery and BRAT score arc important.
Keywords: Intraoperative period; pressure injury; risk factor; prevalence of pressure injury